Produktifitas Ulat Hongkong (Tenebrio molitor) pada Media Pakan yang Berbeda - Hapsari, D. G. P. L.; Fuah, A. M.; Endrawati, Y. C. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
Mealworm is the larva stage of Tenebrio molitor L. beetle which is used for pet feed. The aim of this research was to analyze the effect of feeding medias to support the growth of mealworm. The compared feeding media were 100% dry tofu by product as a control, 100% rice bran, 100% rice husk, 50% dry tofu by product + 50% rice bran, 50% dry tofu by product + 50% rice husk and 50% rice husk + 50% rice bran. Randomized Complete Design was used as the experimental design with 6 treatments with 3 replications for each treatment. The result showed that body weight and body length were not significantly different (P>0.05) among media, but mortality and pupation were significantly different (P<0.05). The feeding media with 50% dry tofu by product + 50% rice bran are better to use because it can increase feed consumption, percentage of pupation, and reduce mortality.